Multiply both sides of the equation by <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify the right side.

Simplify <math><mstyle displaystyle="true"><mn>12</mn><mrow><mo>(</mo><mfrac><mrow><mn>6</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Combine <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>6</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> .

Simplify the expression.

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>24</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Do you know how to Solve for u u/12=6/9? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.